2014
DOI: 10.1111/josh.12194
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Statewide Childhood Body Mass Index Surveillance Program

Abstract: Background Several states have implemented childhood obesity surveillance programs supported by legislation. Representatives from Idaho wished to develop a model for childhood obesity surveillance without the support of state legislation, and subsequently report predictors of overweight and obesity in the state. Methods A coalition comprised of the Idaho State Department of Education and 4 universities identified a randomized cluster sample of schools. After obtaining school administrator consent, measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…This study was cross-sectional in nature, and longitudinal studies to examine change in perceptions over time are needed. Data were collected in a Midwestern state in the United States, and children's frame of reference for judging weight status could have been influenced by their views of typical weights of children in the region (Paul et al 2014). This may be a threat to generalizability of child perception findings to other non-comparable populations.…”
Section: Discussionmentioning
confidence: 99%
“…This study was cross-sectional in nature, and longitudinal studies to examine change in perceptions over time are needed. Data were collected in a Midwestern state in the United States, and children's frame of reference for judging weight status could have been influenced by their views of typical weights of children in the region (Paul et al 2014). This may be a threat to generalizability of child perception findings to other non-comparable populations.…”
Section: Discussionmentioning
confidence: 99%
“…An income eligibility form must be completed for a student to be eligible for Free Level2 and reduced-price meals. Meal status is often used as a measure of individuallevel poverty because of its direct relationship with household income; 10,13,14,[31][32][33] in our analysis, we refer to meal status as ''Poverty MEAL '' when used as a 4-level measure of individual poverty.…”
Section: Instrumentsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Previous research has shown that, in addition to behaviors, socioeconomic factors play an important role in health outcomes among adolescents. 4,[7][8][9][10][11][12][13][14] However, the YRBS does not directly measure poverty. Typical measures of individual socioeconomic status (SES) used for adults such as income, education-level, and occupation cannot be used for children because they usually are still in school, live with a parent or guardian, and often do not know the required information to determine household income.…”
mentioning
confidence: 99%
See 2 more Smart Citations